PROBLEMATIKA DAKWAH DALAM LEDAKAN INFORMASI - Hatta Abdul Malik (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2017)
This research based on qualitative research with islamic communication approach. The results of this research indicate that in the information age has led to an explosion of information. The problematic of the explosion of information can be seen from the increasing need of computer hardware and adequate device for information is a necessity, the information is mixed between important and not important, so it takes the user's sharpness to sort and choose information. The existence of addiction information resulted in users experiencing anxiety dealing with information. In addition, widespread news lies into a serious problem in the explosion of information